Pengaruh Investment Opportunity Set dan Free Cash Flow Pada Kebijakan Dividen dan Nilai Perusahaan - Suartawan, I Gusti Ngurah Putu Adi; Yasa, Gerianta Wirawan (Jurnal Ilmiah Akuntansi dan Bisnis, 2017)
This research is conducted to find out the effect of investment opportunity set and free cash flow towards dividend policy and its impacts on firm value of manufacturing companies registered in Indonesia Stock Exchange during the period of 2011-2013. The samples of this study are 25 manufacturing companies and they were selected by using purposive sampling method. The data is collected through non participants’ observation. Path analysis which is an extension of the multiple linear regression technique is used to analyze data. Based on the data analysis, it was found that, investment opportunity set has positive effects on dividend policy. It refuses the negative hypothesis, free cash flow has positive effects on dividend policy, investment opportunity set has positive effects on firm value, free cash flow has positive effects on firm value, dividend policy has positive effects on firm value, investment opportunity set has effects on firm value  through dividend  policy  and free  cash flow has no  effects on firm value  through  dividend   policy.
Keywords: firm value, investment opportunity set, free cash flow, dividend policy